EVALUATION ON UTILIZATION OF SMALL MARINE FISH TO PRODUCE SURIMI USING DIFFERENT CRYOPROTECTIVE AGENTS TO INCREASE THE QUALITY OF SURIMI - Tri Winarni Agustini; Y. S. Darmanto; Danar Puspita Kurnia Putri (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Quality of surimi (minced meat of fish) usually decrease due to denaturation of protein. Addition of cryoprotective agent such as reducing sugar as anti denaturation of protein is very important during storage of frozen surimi. Recently, development of human lifestyle require healthy food such as utilization of stevia sugar (Stevia rebaudiana) which has low calorie that can be used to replace sorbitol and sucrose during processing of surimi. The purposes of this research are to observe the effect of different cryoprotective agents before and during storage as well as the effect of storage on quality of frozen surimi fish based on pH value, water holding capacity (WHC), gel strength and organoleptic value. Materials used was surimi made from kurisi (Nemipterus sp.), stevia sugar, sorbitol and sucrose. Research method used was experimental laboratory with research design of Completely Randomized Design with split plot in time. The main plot was difference of cryoprotectant (stevia sugar 0.6%; sorbitol 4%; sucrose 4%). The product was analysed every 15 days starting from 0 to 45 days storage at – 10oC. The results showed that different cryoprotectants agent gave no significant effect before storage treatment proceed. In addition during storage, the different of cryoprotectant gave significant effect to WHC and gel strength (SSS=1356,416; SS=1458,525; S=1511,307 g.cm) but not for pH. The organoleptic value for appearance on 15 days storage was SSS=7; SS=7; S=6,56 and Folding test showed SSS=7; SS=7.78; S=7,89)